2020
DOI: 10.1002/jlb.3a0220-097r
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 antagonism results in altered interactions between platelets and regulatory T cells during sepsis

Abstract: Sepsis is a complex clinical condition resulting from a serious bloodstream infection. With mortality rates as high as 50%, improved treatments are needed. Regulatory T cells (Tregs), a subset of T lymphocytes, promote the resolution of inflammation. Septic patients have elevated levels of circulating Tregs. Platelets influence the proliferation and activation of Tregs in vitro. However, modulating platelet‐Tregs interaction during sepsis may restraing Treg proliferation, leading to the restoration of immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Leukocytes play a fundamental role in innate and adaptive immunity, wound healing, tumor surveillance, and tissue remodeling. Platelets therefore circulate in a quiescent state and were rapidly activated by invading pathogens and other stimuli [ 31 ]. Measurement of miRNAs (127 and 320a) revealed this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes play a fundamental role in innate and adaptive immunity, wound healing, tumor surveillance, and tissue remodeling. Platelets therefore circulate in a quiescent state and were rapidly activated by invading pathogens and other stimuli [ 31 ]. Measurement of miRNAs (127 and 320a) revealed this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The cecal ligation and double puncture (CLP) procedures were performed on under anesthesia with isoflurane (2 ± 4% induction in chamber and 1 ± 2% maintenance in mask) as described previously ( 26 , 31 33 ). Following midline laparotomy, the cecum was identified, the mesentery trimmed, and the stalk joining the cecum to the large intestine ligated.…”
Section: Methodsmentioning
confidence: 99%
“…They act on both the innate and adaptive immune systems, dampening immune functions, causing immuno-paralysis, and eventually leading to MODS and death in sepsis (14,18,(122)(123)(124)(125). Intervention strategies (Tables 3 and 4), such as human recombinant cytokines (IL-15 and IL-36) (59,101), blocking phenotypes or chemokines [neuropilin (Nrp)-1, CTLA-4, lymphocyte activation gene (LAG)-3, and chemokine (C-X-C motif) ligand (CXCL) 4)] (50,58,77,82), nutrients (glutamine) (107), inhibiting molecules [sema3A, tissuenonspecific alkaline phosphatase (TNAP), Sirtuin1, P2Y12, COX-2, and poly ADP-ribose polymerase (PARP)] (48,51,102,(111)(112)(113), as well as even clinical therapeutics (high-volume hemofiltration, immunoglobulin, fresh frozen plasma, stem cells, and ulinastatin) (41,114,115,117,118) and traditional Chinese medicine (TCM) (electroacupuncture and tanshinone IIA) (103,106), can increase the chance of survival by inhibiting the heterogeneous characteristics of Treg-induced immunosuppression. Alternatively, other studies have shown improved outcomes in sepsis by increasing the heterogeneous characteristics of Tregs to inhibit sepsis-induced SIRS through intervention strategies such as human recombinant cytokines (IL-38 and IL-7) (96,97), blocking phenotypes or cytokines (CD28 and IL-3) (81,95), nutrients (arginine and fiber cellulose) (108,109), and others (bilirubin, ITK inhibitor, miR-126, maresin1, excretory-secretory products of Trichinella spiralis adult worms, and adipose-derived mesenchymal stem cell-derived exosomes) (19,…”
Section: Treg Heterogeneity In Sepsismentioning
confidence: 99%